2023
DOI: 10.3390/horticulturae9060655
|View full text |Cite
|
Sign up to set email alerts
|

Avermectin Trunk Injections: A Promising Approach for Managing the Walnut Husk Fly (Rhagoletis completa)

Abstract: This study examined the larvicidal effect of trunk-injected abamectin and emamectin benzoate against the walnut husk fly (Rhagoletis completa Cresson, 1929). Walnut trees in two locations in two years were injected with the pesticides at different concentrations. For the toxicokinetic studies, the active ingredient content was measured in the leaves, flowers, husks, and kernels, using a UHPLC-MS/MS analytical method. The walnut husk fly infestation rates were between 3 and 70% and 10 and 34% for abamectin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In 2004, Calzarano's experiment proved that grapevines receiving trunk injection of Cyproconazole were in better nutritional condition and had higher yield and lower mortality rate than those without such injections, demonstrating the beneficial effect of fungicide injection through the trunk on root rot [41]. Injecting pesticides or antibiotics into a tree trunk has proven to be an efficient method for treating diverse tree diseases and preventing the invasion of harmful pests [6,[42][43][44][45]. In 2013, Akinsanmi's experiments showed that biannual application of phosphite during autumn and spring root wash periods effectively controlled tree decline in Australian macadamia trees [46].…”
Section: The Development Process Of Tree Trunk Injectionmentioning
confidence: 99%
“…In 2004, Calzarano's experiment proved that grapevines receiving trunk injection of Cyproconazole were in better nutritional condition and had higher yield and lower mortality rate than those without such injections, demonstrating the beneficial effect of fungicide injection through the trunk on root rot [41]. Injecting pesticides or antibiotics into a tree trunk has proven to be an efficient method for treating diverse tree diseases and preventing the invasion of harmful pests [6,[42][43][44][45]. In 2013, Akinsanmi's experiments showed that biannual application of phosphite during autumn and spring root wash periods effectively controlled tree decline in Australian macadamia trees [46].…”
Section: The Development Process Of Tree Trunk Injectionmentioning
confidence: 99%
“…Endotherapy treatment is often used in urban plant protection for deciduous trees. Several experiments have demonstrated the successful use of trunk injection against different pests [21][22][23][24][25]. Walnut trees have been effectively treated with abamectin against the walnut husk fly (Rhagoletis completa) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments have demonstrated the successful use of trunk injection against different pests [21][22][23][24][25]. Walnut trees have been effectively treated with abamectin against the walnut husk fly (Rhagoletis completa) [24]. The tiger longicorn beetle (Xylotrechus chinensis) is a pest to Mulberry (Morus sp.)…”
Section: Introductionmentioning
confidence: 99%